PENGARUH PENDIDIKAN KESEHATAN TERHADAP ENGETAHUAN MASYARAKAT TENTANG PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN MELONGUANE TIMUR LINGKUNGAN II KABUPATEN TALAUD - Ludong, Joice; Stefanus Timah; Olvin Manengkey (Yayasan Syalom Cipta Sumikolah, 2025)
The sample in this research was determined by the purposive sampling method using the Based on the research results, the influence of health education on public knowledge regarding prevention of dengue hemorrhagic fever (DBD) in the East Melonguane Village, Environment II, Talaud Regency, using the Wilcoxon statistical test, obtained a p-value = 0.000 < 0.05. It was identified that the community's knowledge about preventing dengue hemorrhagic fever (DBD) before being given health education in Melonguane Timur Subdistrict, Environment II, Talaud Regency, most of the knowledge was poor, as many as 16 respondents (100%), identified the community's knowledge about preventing dengue hemorrhagic fever (DBD) after being given education. Health in Melonguane Timur Subdistrict, Environment II, Talaud Regency, most of the knowledge is good, as many as 9 respondents (56.3%) and poor knowledge as many as 7 respondents (43.8%). The conclusion in this study is that there is a significant influence of Health Education on Community Knowledge about the Prevention of Dengue Hemorrhagic Fever (DHF) in Melonguane Timur Ward II, Talaud Regency with a value of p = < 0.05. hoped that it can provide information and knowledge for the people of East Melonguane Ward, Environment II, related to increasing public awareness about the importance of eradicating mosquito nests.